Effect of Cotton Leafroll Dwarf Virus on Physiological Processes and Yield of Individual Cotton Plants - Parkash, Ved; Sharma, Divya Bhanu; Snider, John; Bag, Sudeep; Roberts, Phillip; Tabassum, Afsha; West, Dalton; Khanal, Sameer; Suassuna, Nelson; Chee, Peng (Frontiers in Plant Science, 2021)
The Cotton leafroll dwarf disease (CLRDD) caused by cotton leafroll dwarf virus (CLRDV) is an emerging threat to cotton production in the United States. The disease was first reported in Alabama in 2017 and subsequently has been reported in ten other cotton producing states in the US, including Georgia. A field study was conducted at field sites near Tifton, Georgia in 2019 and 2020 to evaluate leaf gas exchange, chlorophyll fluorescence, and leaf temperature responses for a symptomatic cultivar (diseased plants observed at regular frequency) at multiple stages of disease progression and for asymptomatic cultivars (zero percent disease incidence observed). It was found that net photosynthetic rate (An), stomatal conductance (gs), and efficiency of the thylakoid reactions declined substantially, whereas leaf temperature significantly increased at advanced stages of the disease. Net photosynthesis was substantially more sensitive to disease-induced declines in gs than the thylakoid reactions. Symptomatic plants with more advanced disease stages remained stunted throughout the growing season, and yield was reduced by CLRDD due to reductions in boll number per plant and declines in boll mass resulting from fewer seeds per boll. Asymptomatic cultivars exhibited more conservative gas exchange responses than apparently healthy plants of the symptomatic cultivar but were less productive. Overall, it is concluded that CLRDV limits stomatal conductance and photosynthetic activity of individual leaves, causing substantial declines in productivity for individual plants. Future studies should evaluate the physiological contributors to genotypic variation in disease tolerance under controlled conditions.